Studies on the formation and forming mechanism of the related substance E in potassium clavulanate production by HPLC-MS/MS (Brazilian Journal of Pharmaceutical Sciences, 2014)
The objective of this study was to investigate the formation and forming mechanism of the related substance E in potassium clavulanate production. The impurity with retention time of 11.1 min in potassium clavulanate final product was confirmed as the related substance E by high performance liquid chromatography with tandem mass spectrometric detection (HPLC-MS/MS).The related substance E analysis during the production of clavulanic acid showed that this impurity could be formed during both the fermentation and purification processes, especially in the later fermentation stage, filtration concentration and back-extraction procedure. Clavulanic acid was the precursor of the related substance E. Studies on its forming mechanism showed that the related substance E was formed by the combination of the imino group of one molecule of clavulanic acid with the carboxyl group of another molecule of clavulanic acid with the opening of β-lactam ring. Results of a multi-factor orthogonal test confirmed that the concentration of clavulanic acid was the dominant factor to accelerate the reaction, while the temperature was another contributing factor. The pH 5.0-6.5 had little impact on the generation of the related substance E.